Real Exchange Rate and Inflation: An Empirical Assessment of the Nigerian Experience - Oriavwote, Victor E.; Eshenake, Samuel J. (Richtmann Publishing, 2012)
The objective of the paper has been to assess the relationship between the real exchange rate and inflation in Nigeria. Usingdata covering the period between 1970 and 2010, the cointegration test result shows a long run relationship between inflation and thereal exchange rate. The satisfactory speed of adjustment indicated by the error correction model further supports this long runrelationship. The result showed that both domestic and imported inflation appreciated the real exchange rate. The ARCH result indicatesthe persistence of volatility between the rate of inflation and the real exchange rate. An indication that the real exchange rate in Nigeriahas been susceptible to fluctuations in the rate of inflation. Policy makers should thus, not rely only on policies to stabilize real exchangerate by targeting inflation, but should employ domestic policies to increase export and production of previously imported inputs to reducethe problem of imported inflation.